Peristicta aeneoviridis Calvert, 1909 and P. forceps Hagen in Selys, 1860: redescriptions and a new synonymy (Zygoptera: Protoneuridae) - Pessacq, Pablo (2007)
Peristicta misionera Jurzitza is considered a synonymy of P. aeneoviridis Calvert, holotype of P. aeneoviridis is redescribed. P. forceps Hagen In Selys male is redescribed, female and larvae are described for the first time. Kennedy’s drawing of holotype genital ligula is reproduced.